Blending Cultures in BTS’s “Blood Sweat and Tears” - Daniel Nedelcu (Linguaculture)
Pop culture often functions as a vehicle for what is deemed “high culture,” either through mentions and representations, or adaptations and recontextualizations. Hallyu, the wave of Korean cultural products overtaking the world market, including emerging markets such as the Romanian one, abounds in examples of cultural blending or hybridization. BTS, the Korean band who have made K-pop a truly global phenomenon, exemplify the blending of high culture with pop culture, as well as the blending of Eastern and Western cultures, especially in the video to their 2016 song “Blood Sweat & Tears.”